Photoshop Studio with Bert Monroy : digital painting - Monroy, Bert (California : New Riders Publishing, 2008)
One of the most talented digital artists working in the medium shares his secrets for creating stunning art using Adobe Photoshop. A master class for the experienced Photoshop artist, this beautifully illustrated guide not only shows how to construct digital images, but also the painstaking refinement process required to create truly magnificent work. With the culmination of years of experimentation, Bert Monroy demonstrates step-by-step the essential techniques you'll need to build awe-inspiring photorealistic paintings. Learn how to: - Effectively use the Brushes palette and other Photoshop tools - Master alpha channels, layers, selections, filters, masks, and clipping paths - Use highlights and shadows effectively to set the mood and add dimension - Understand perspective and create eye-catching compositions - Organize your workflow, take photographs, and collect reference materials to produce an accurate rendering of the subject Download bonus chapters at: www.peachpit.com/digitalpainting.
Foreword -- Introduction -- How to Use This Book -- 1. The Workflow -- 2. Lights and Shadows -- 3. Oakland -- 4. Shoe Repair -- 5. Old Chair -- 6. Red Truck -- 7. Oyster Bar -- 8. Lunch in Tiburon -- 9. Damen -- 10. Tutorials -- Index
Includes index.
Keywords: ADOBE PHOTOSHOP